2017
DOI: 10.2147/ijn.s123648
|View full text |Cite
|
Sign up to set email alerts
|

Silver-loaded nanotubular structures enhanced bactericidal efficiency of antibiotics with synergistic effect in vitro and in vivo

Abstract: Antibiotic-resistant bacteria have become a major issue due to the long-term use and abuse of antibiotics in treatments in clinics. The combination therapy of antibiotics and silver (Ag) nanoparticles is an effective way of both enhancing the antibacterial effect and decreasing the usage of antibiotics. Although the method has been proved to be effective in vitro, no in vivo tests have been carried out at present. Herein, we described a combination therapy of local delivery of Ag and systemic antibiotics treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Besides, Figure 1F showed the release kinetics of Ag + ions from Ag@TiO 2 -NTs detected by ICP-AES on days 1, 3, 5, 7 and 10 was 0.202, 0.046, 0.012, 0.009, and 0.005 ppm, respectively, which decreased gradually after the first 3 days. As with the initial concentration and release kinetics of Ag + ions in our previous study, 10 our Ag@TiO 2 -NTs could have the excellent antibacterial effect when combined with antibiotics. Meanwhile, the size of AgNPs is an important factor that influences the cytotoxicity.…”
Section: Results and Discussion Surface Characterization And Ag + Relsupporting
confidence: 69%
See 2 more Smart Citations
“…Besides, Figure 1F showed the release kinetics of Ag + ions from Ag@TiO 2 -NTs detected by ICP-AES on days 1, 3, 5, 7 and 10 was 0.202, 0.046, 0.012, 0.009, and 0.005 ppm, respectively, which decreased gradually after the first 3 days. As with the initial concentration and release kinetics of Ag + ions in our previous study, 10 our Ag@TiO 2 -NTs could have the excellent antibacterial effect when combined with antibiotics. Meanwhile, the size of AgNPs is an important factor that influences the cytotoxicity.…”
Section: Results and Discussion Surface Characterization And Ag + Relsupporting
confidence: 69%
“…9,11 For this method, the concentration of the silver salt plays a very important role for both the size and the shape of AgNPs which can be regulated by changing the concentration of AgNO 3 solution. 10,47 Therefore, the size of AgNPs always be around 20 nm for the reason that the concentration of the AgNO 3 solution was 1M.…”
Section: Results and Discussion Surface Characterization And Ag + Relmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also studies using systemic antibiotics treatment and local delivery of AgNPs in vitro and in vivo. The results indicated that AgNPs increased antibacterial efficiency of antibiotics, reduced their usage of and shortened their administration time [ 107 , 108 ]. On the other hand, metal ions, such as Cu and Zn ions, could also act as environmental drivers of antibiotic resistance via co-occurrence of metal resistance and antibiotic resistance genes in animal isolates of multidrug-resistant bacteria [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the biofilms are the physical barriers, which is composed by a three-dimension extracellular polymeric matrix, to protect the inside bacteria from attack by host defense and antibiotics 5. As a result, 1,000-fold higher antibiotic dosage and extended antibiotic therapy may be required to kill the bacteria in biofilm than the common planktonic bacteria, especially for the antibiotics-resistant bacteria strain like methicillin-resistant Staphylococcus aureus (MRSA), etc 6,7. Therefore, it is an urgent issue to inhibit the formation of biofilm at the earliest step by using physical and/or chemical methods 8.…”
Section: Introductionmentioning
confidence: 99%